Clinical Impact of Antipolyethylene Glycol (PEG) Antibody in Hematological Patients Administered PEGylated‐Granulocyte Colony‐Stimulating Factor - Okada, Naoto; Taro, Shimizu; Ando, Hidenori; Nakamura, Shingen; Goda, Mitsuhiro; Abe, Masahiro; Kitahara, Takashi; Ishida, Tatsuhiro; Ishizawa, Keisuke (Clinical pharmacology in drug development, 2023)
Polyethylene glycol (PEG) is a polymer covalently attached to proteins to improve their half‐life and efficacy. We previously reported that the PEGylated granulocyte colony‐stimulating factor (PEG‐G‐CSF) is immunogenic, which could adversely impact drug efficacy and safety in animal models. Here, we analyzed the relationship between anti‐PEG antibody titers and the clinical impact of PEG‐G‐CSF in 19 hematological patients. A gradual decrease of anti‐PEG antibody titers from baseline was observed after PEG‐G‐CSF administration. Of the 19 participants, 10 were assessed for noninfectious fever after the first administration of PEG‐G‐CSF and three experienced this reaction. The receiver operating characteristic curve revealed that the cut‐off values of pretreated anti‐PEG IgM and IgG titers for noninfectious fever were set at 5.0 and 96.6 U/mL, respectively. All patients who experienced noninfectious fever had anti‐PEG antibody titers above this cut‐off value (P = .033). An enzyme‐linked immunosorbent assay revealed that some anti‐PEG antibodies in patients with anti‐PEG antibody titers above the cut‐off value reacted with the PEGylated liposome. These results indicate the reactivity of the anti‐PEG antibodies to PEGylated therapeutics observed in hematologic patients and the possibility of the relationship between high titers of anti‐PEG antibodies and the development of adverse events after PEG‐G‐CSF administration.